Effect of TiO2 on Orange Peel Activated Carbon Composite in Reducing Carbon Monoxide and Hydrocarbon Gas Emissions - Ya' Muhammad Arsyad; Dwiria Wahyuni; Nurhasanah Nurhasanah; Bintoro Siswo Nugroho; Riza Adriat; Agus Prasetiono; Wahyu Tri Hidayat (Universitas Andalas, 2023)
study aims to see the effect of adding TiO2 on activated carbon as a material for reducing CO and HC gas emissions. Activated carbon (AC) was synthesized from orange peel waste at a carbonization temperature of 600 with a 10% (w/v) ZnCl2 activator. Composite AC/TiO2 was prepared by a simple mixing method. This process obtained TiO2-modified activated carbon material with variations in TiO2 concentrations of 0%, 10%, 15%, 20%, and 25%. Scanning Electron Microscope (SEM) was performed to obtain information on the AC/TiO2 surface morphology. In the application as a CO and HC gas emission reduction material, the results of mixing AC/TiO2 are mixed with a 10% (w/v) solution of Polyvinyl Alcohol (PVA) as an adhesive and molded in the shape of a filter with two variations hole sizes with a diameter of 1 cm and 0.3 cm. Composite filter performance tests were carried out using a gas analyzer. The best result for reducing gas emissions occurred at a concentration of TiO2 15% with reduction power to reduce CO gas emission up to 53.79% and HC gas emission up to 55.57%.